2013
DOI: 10.1177/2048872612475270
|View full text |Cite
|
Sign up to set email alerts
|

Is the difference in outcome between men and women treated by primary percutaneous coronary intervention age dependent? Gender difference in STEMI stratified on age

Abstract: on behalf of the Zwolle myocardial infarction study group Abstract Aim: Poorer outcomes in women with ST-elevation myocardial infarction (STEMI) are often attributed to gender differences in baseline characteristics. However, these may be age dependent. We examined the importance of gender in separate age groups of patients with STEMI undergoing primary percutaneous coronary intervention (PPCI). Methods and results: Data of 6746 consecutive patients with STEMI admitted for PPCI between 1998 and 2008 in our hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
80
1
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 53 publications
12
80
1
6
Order By: Relevance
“…In our study, young women seem to be more prone to VTE while men present more frequently with ATE, in agreement with previously reported data in which, at a younger age, there is an overwhelming male majority in patients with acute myocardial infarction (MI) (22). Moreover, premenopausal women have a much lower incidence of heart disease compared to men of the same age explained mostly by the hormonal profile (23).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, young women seem to be more prone to VTE while men present more frequently with ATE, in agreement with previously reported data in which, at a younger age, there is an overwhelming male majority in patients with acute myocardial infarction (MI) (22). Moreover, premenopausal women have a much lower incidence of heart disease compared to men of the same age explained mostly by the hormonal profile (23).…”
Section: Discussionsupporting
confidence: 92%
“…(16) The mean times investigated showed delay in the access to health services, mainly for women, which remains long. (6) Women may underestimate the risk of heart disease (17) and experience symptoms that are not always typical of the disease, (18) reasons that contribute to a greater delay.…”
Section: Discussionmentioning
confidence: 99%
“…Funakoshi et al 12 evaluated Japanese patients (2845 women and 6843 men undergoing first coronary revascularization; PCI or coronary artery bypass grafting) and found that the coronary risk factor burden appeared greater in women than in men, despite the fact that women had a lower incidence of repeated revascularization compared with men. Otten et al 13 studied 4991 men and 1755 women admitted to the hospital for PCI. Patients were stratified into 2 groups, <65 years (young group) and 65 years (elderly).…”
mentioning
confidence: 99%